Electrically pumped single-defect light emitters in WSe2. (27th June 2016) - Schwarz, S; Kozikov, A; Withers, F; Maguire, J K; Foster, A P; Dufferwiel, S; Hague, L; Makhonin, M N; Wilson, L R; Geim, A K; Novoselov, K S; Tartakovskii, A I
Abstract: Recent developments in fabrication of van der Waals heterostructures enable new type of devices assembled by stacking atomically thin layers of two-dimensional materials. Using this approach, we fabricate light-emitting devices based on a monolayer WSe2, and also comprising boron nitride tunnelling barriers and graphene electrodes, and observe sharp luminescence spectra from individual defects in WSe2 under both optical and electrical excitation. This paves the way towards the realisation of electrically-pumped quantum emitters in atomically thin semiconductors. In addition we demonstrate tuning by more than 1 meV of the emission energy of the defect luminescence by applying a vertical electric field. This provides an estimate of the permanent electric dipole created by the corresponding electron–hole pair. The light-emitting devices investigated in our work can be assembled on a variety of substrates enabling a route to integration of electrically pumped single quantum emitters with existing technologies in nano-photonics and optoelectronics.